Enhanced Oral Bioavailability of Celecoxib Nanocrystalline Solid Dispersion based on Wet Media Milling Technique: Formulation, Optimization and In Vitro/In Vivo Evaluation - Zhuang Ding; Lili Wang; Yangyang Xing; Yanna Zhao; Zhengping Wang; Jun Han (Pharmaceutics, 2019)
Celecoxib (CLX), a selective COX-2 inhibitor, is a biopharmaceutics classification system (BCS) class II drug with its bioavailability being limited by thepoor aqueoussolubility. The purpose of this study was to develop and optimize CLX nanocrystalline(CLX-NC) solid dispersion prepared by the wet medium millingtechnique combined with lyophilizationto enhance oral bioavailability. In formulation screening, the resulting CLX-NC usingpolyvinylpyrrolidone (PVP) VA64 and sodiumdodecyl sulfate (SDS) as combined stabilizers showed the minimum particle size and a satisfactory stability. The formulation and preparation processwere further optimized by central composite experimentaldesign with PVP VA64 concentration (X1), SDS concentration (X2) and milling times (X3) as independent factors and particle size (Y1), polydispersity index (PDI, Y2) and zeta potential (Y3) as response variables. The optimal condition was determined as a combination of 0.75% PVP VA64, 0.11% SDS with milling for 90 min.The particle size, PDI and zeta potential of optimized CLX-NC were found to be 152.4 ± 1.4 nm, 0.191 ± 0.012 and −34.4 ± 0.6 mV, respectively. The optimized formulation showed homogeneous rod-like morphology as observed by scanning electron microscopy and was in a crystalline state as determined by differential scanning calorimetry and powder X-ray diffraction. In a storage stability study, optimized CLX-NC exhibited an excellent physical stability during six months’ storage at both the refrigeration and room conditions. In vivo pharmacokinetic research in Sprague-Dawley ratsdisplayed that Cmax and AUC0−∞ of CLX-NC were increased by 2.9 and 3.1 fold, compared with physical mixture. In this study, the screening and optimizing strategy of CLX-NC formulation represents a commercially viable approach forenhancing the oral bioavailability of CLX.